SOME ETIOLOGIC RISK FACTORS FOR MULTIPLE SCLEROSIS AMONG PRYKARPATTIA REGION INHABITANTS - Негрич, Т. І.; Гриб, В. А.; Оринчак, Л. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the results of studying the cases of 242 patients with multiple sclerosis (MS) of Carpathian residents. Studied some etiologic risk factors of MS, as well as their influence on the peculiarities of demyelinating process. It is shown that such factors as high body mass index (BMI) of 20, smoking should be considered when counseling patients with MS as they may contribute to the progression of the disease.